Perancangan Sistem Informasi Kerja Paruh Waktu Mahasiswa dengan Lingkup Internal Program Studi X - Chandra, Jonathan; Loekito, Jimmy (Jurnal Ilmiah Matrik, 2025)
The information system in the form of part-time job vacancies in the scope of study programme X is one of the containers that is needed both from employers (lecturers) and job seekers (students). The information system regarding part-time work in study programme X is able to provide convenience for employers in finding workers who are in accordance with what they need and also provide opportunities in the form of experience for job seekers in study programme X. This research work begins with a system design design with predetermined limits based on observations of the X study programme which is used as a benchmark. The development of this information system is determined using the prototype development method because of the short development time and must be able to be used while the development itself takes place. After obtaining the limitations from the observation results, a database system design will be carried out for the purposes of this research information system application which will be applied to the system. The next step is the information system design process which is broken down into two parts, namely the front-end and back-end parts. For testing this information system itself using the black box testing method with the main target, namely the original user as the respondent